FAMILY FOOD SECURITY IMPROVEMENT BY USING POSITIVE DEVIANCE APPROACH - Handayani, Trini (International Journal of Research -GRANTHAALAYAH, 2021)
Background and Objective: Food is a basic human need whose fulfilment cannot be substituted with other materials. Food security is perfectly adequate for a country and its individuals, reflected insufficient food availability, both in terms of its quantity, quality, safe, diverse, nutritious, equitable and affordable. Toddler still had low nutrition and malnutrition of more than 18 % of children throughout Indonesia. The purpose of this study was to assess the Positive Deviance parenting towards toddler in Cianjur. Material and Method: An Observation of the family with low economics levels but have a good nutrition toddler. The sample was 15 families. Interview and observation of the family are used to guide the study. The instruments used were structural and un-structural interviewing. The participant had their economic and nutrition assessed through financial and food sections. The data analysis consisted of the answer to the question that has been asked with using qualitative study. Result: In this study, some individuals or groups have behaviour and strategy that are unusual but successful and have allowed them to find better solutions to their problems. PD is based on the belief that it is solving problems that society faces. Conclusion: PD in nutrition improvement program aims to have under-five children with low nutrition and malnutrition, finding positive deviance behaviour in the community. This behaviour is then followed by the families of low-nourished and malnourished children, increasing their nutritional status.